The future energy mix paradigm: How to embed large amounts of wind generation while preserving the robustness and quality of the power systems - Estanqueiro, Ana (2010)
The 2001/77/CE Renewable Energies European Directive together with Kyoto Protocol ratification by many countries, supported by some Governments vision and strong objectives on the reduction of external oil dependence, put Europe and other developed economies in the front line to achieve a remarkable wind energy penetration within ten years time. These goals will not be achieved without technical costs and risks, but mainly,without a careful planning and assessment of the power system behaviour with large amounts of wind generation (SRA, 2008; IEAWind, 2008).These days, one of the most relevant difficulties the wind sector faces was caused by this technology own extreme success. The high capacity installed in the last decade introduced a brand new set of power system technological concerns that recently became one of the more referenced subjects among developers, network planners and system operators. These concerns are not anymore a negligible distribution grid integration issue that some years ago the experts tended not to give too much relevance since they were easily solved and even more easily avoided through good design and planning, but this is a real power system operation and planning challenge (Holttinen et al, 2009): will the power systems be capable to cope with the specificities of the wind power production in large quantities (aka “high penetration”) without requiring new wind park models, system operation tools,increased performance of the wind turbines or even a change in the Transmission System Operators (TSOs) conventional mode of operation? The recent concern of the TSOs is very legitimate, since it is their responsibility to design and manage the power system global production and its adjustment to the consumer loads as well as to assure the technical quality of the overall service, both in steady-state and under transient occurrences.